Immunoglobulin G immune response to SARS-CoV-2 vaccination in people living with multiple sclerosis within Multiple Sclerosis Partners Advancing Technology and Health Solutions. (June 2022) - Cohen, Jeffrey A; Bermel, Robert A; Grossman, Cynthia I; Hersh, Carrie M; Hyland, Megan; Mowry, Ellen M; Naismith, Robert; Naylor, Maria L; Nicholas, Jacqueline; Rajbhandar, Rajani; Singh, Carol M; Tintorè, Mar; et al.
Background: The impact of multiple sclerosis (MS) disease-modifying therapies (DMTs) on SARS-CoV-2 vaccination response is uncertain. Methods: Post-SARS-CoV-2 vaccination blood samples across multiple DMTs were tested for SARS-CoV-2 immunoglobulin G (IgG) response. Results: Three hundred twenty-two people with MS were included; 91.9% received an mRNA vaccine. Post-vaccination reactive IgG rates (IgG index > 1) were 40% for anti-CD20 (32/80 patients); 41% for sphingosine 1-phosphate receptor modulators (S1PRM, 16/39); and 100% for all other classes, including the no DMT group. Conclusion: Anti-CD20 therapies and S1PRMs reduce IgG response to SARS-CoV-2 vaccination; IgG response is preserved with other DMTs.